PROFIL METABOLIT SERTA AKTIVITAS ANTIOKSIDAN PADA AKAR DAN DAUN TANAMAN HANJELI (Coix lacryma-jobi L.) DESA WISATA HANJELI SUKABUMI - Zahra Apriyani Pratiwi, - (2023)
Hanjeli (Coix lacryma-jobi L.) has been widely used as a traditional medicine in various countries. This plant is known to contain metabolites that vary in each region. Desa Wisata Hanjeli, Sukabumi Regency, is an educational destination engaged in the cultivation of local hanjeli plants. The pupose of the study to obtain profiles of metabolites contained in the roots and leaves and leaves of hanjeli cultivars of ketan and batok as well as antioxidant activity in the roots and leaves of hanjeli batok. Samples of roots and leaves were taken from Desa Wisata Hanjeli, Sukabumi Regency. Samples were extracted using the maceration method with ethanol p.a as solvent. 70%. The metabolites of hanjeli roots and leaves were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) and identified using the WILLEY09TH library. The results showed that the root of the hanjeli ketan contains 9 compounds, while the root of the hanjeli batok contains 5 compounds. Both hanjeli roots are dominated by 4-vinylphenol compounds (hanjeli ketan roots = 24.40%, hanjeli batok roots = 35.12%) which belong to the phenolic group. Hanjeli ketan leaves contain 8 compounds which are dominated by methyl linoleic compounds (17.78%) which belong to the fatty acid group, while hanjeli batok leaves contain 9 compounds which are dominated by methyl linoleic acid compounds (12.49%) which belong to the fatty acid group. The IC50 value of the root extract (315.72 ppm) and leaves (390.64 ppm) of hanjeli batok showed antioxidant activity which was classified as a weak category.This study showed that there were differences in the content of metabolites in the roots and leaves of hanjeli in different cultivars. The antioxidant activity of the root was higher than that of the hanjeli batok leaf.